Inferior vena cava filter use in pregnancy. should the decision regarding filter type be made in a multidisciplinary manner?. (18th April 2012) - Naz, A; Gibson, J; Gallagher, A
Abstract : The use of Inferior Vena Cava (IVC) Filters is recommended in patients with massive Pulmonary Thromboembolism(PTE) treated with thrombolysis or embolectomy.1 Depending on the clinical situation, a temporary (retrievable) or a permanent filter may be used. In pregnant women, the use of a retrievable filter appears more appropriate as the hypercoagulability and duration of anticoagulant therapy is temporary in these younger patients.2 Whereas this device may be beneficial in preventing recurrent PTE in high risk cases, there is limited data on its optimal duration in pregnancy and puerperium. We present a case of massive PTE involving both pulmonary arteries and right ventricle at 10 weeks gestation. After placement of a temporary IVC filter, successful thoracotomy and surgical embolectomy was performed. Due to the reported long term risks and the variable retrieval success rates of these filters after 12 weeks use, the Cardiothoracic surgeon and Radiologists were keen on the filter removal in pregnancy or immediately postpartum. However, the hypercoagulable state of pregnancy and puerperium in general and the high risk nature of this case in particular led to the Obstetric recommendation of prolonging the duration of filter use till the risk of recurrent PTE had subsided. In this review, we have summarised the available evidence regarding the use of retrievable IVC filters in pregnancy. Should the decision regarding filter type be made in a multidisciplinary manner?